2012
DOI: 10.1038/srep00763
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of HIV-1 interfering factors in monocyte-derived macrophages stimulated with polarizing cytokines or interferons

Abstract: HIV-1 replication in macrophages can be regulated by cytokines and infection is restricted in macrophages activated by type I interferons and polarizing cytokines. Here, we observed that the expression levels of the cellular factors Trim5α, CypA, APOBEC3G, SAMHD-1, Trim22, tetherin and TREX-1, and the anti-HIV miRNAs miR-28, miR-150, miR-223 and miR-382 was upregulated by IFN-α and IFN-β in macrophages, which may account for the inhibiting effect on viral replication and the antiviral state of these cells. Exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
71
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(74 citation statements)
references
References 64 publications
(110 reference statements)
3
71
0
Order By: Relevance
“…Examination of cellular expression revealed high levels of Trex1 in immune cells, which were highly induced by proinflammatory stimuli and not by anti-inflammatory cytokines or growth factors in macrophages. This is concurrent with the observation made in human monocyte-derived macrophages in which Trex1 was also upregulated after proinflammatory stimuli (29). Additionally, it has also been reported that Trex1 is upregulated by genotoxic drugs (30,31), indicating that Trex1 is needed for both pathogen DNA degradation and also small strands of nuclear DNA originated from genotoxicity.…”
Section: Discussionsupporting
confidence: 85%
“…Examination of cellular expression revealed high levels of Trex1 in immune cells, which were highly induced by proinflammatory stimuli and not by anti-inflammatory cytokines or growth factors in macrophages. This is concurrent with the observation made in human monocyte-derived macrophages in which Trex1 was also upregulated after proinflammatory stimuli (29). Additionally, it has also been reported that Trex1 is upregulated by genotoxic drugs (30,31), indicating that Trex1 is needed for both pathogen DNA degradation and also small strands of nuclear DNA originated from genotoxicity.…”
Section: Discussionsupporting
confidence: 85%
“…We focused the analysis of restriction factors to HIV, based on the work of Cobos Jimenez et al (26). We observed that triggering of MDMs by the TLR3 and -4 agonists poly(I·C) and LPS, respectively, resulted in the upregulation of all restriction factors examined and in the suppression of cyclophilin, a cellular factor that is incorporated into viral particles.…”
Section: Resultsmentioning
confidence: 99%
“…We also investigated the role of anti-HIV-active IFN-␣ (34) and well-known HIV restriction factors (26). Neutralizing the IFN axis reversed the anti-HIV effects only modestly when triggering the TLR2 pathway; this occurred to a greater extent when triggering the TLR3 and -4 pathways but only minimally when triggering the TLR8 pathway.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations prompted us to examine whether endogenous APOL1 expressed in differentiated and IFN-␥-stimulated U937 cells contributes to anti-HIV-1 activity. However, interferon-stimulated macrophages express a multitude of restriction factors and microRNA (miRNAs) that affect HIV-1 replication (63), and thus, it may be challenging to elucidate the contribution of APOL1 under such conditions. Nevertheless, we have established U937 cell lines that stably express APOL1 shRNA.…”
Section: Discussionmentioning
confidence: 99%